Buku vs e-buku: transformasi era digital - Awang, Nor Hazidah (Persatuan Pustakawan Malaysia, 2010)
Technology has a polarization effect and it is something we should accept. Those who are skilled will continue to compete in line with technology development. The e-book is one of the technology which will change the format of information. This article will look into the usage of books and e-books.